(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the prevalence of low back pain in medical students of United Medical and Dental College Karachi. Methods: This cross sectional study was conducted from 22nd March 2021 to 22nd January 2022 in department of Orthopaedics, United medical and dental college Karachi. The data was collected from medical students of MBBS studying in United Medical and Dental College Karachi. The data was collected with the help of modified version of Standardized Nordic questionnaire. Participants were asked for any discomfort, pain and ache in lower back at any time during the last 7 days and 12 months. (period prevalence) Results: We enrolled 400 medical students of MBBS for this study but 388 participants completed and returned the questionnaire. The mean age of our study sample was 21.36 ± 1.59 years. Female students were 240(61.85 %) and males were 148(31.95. The 12 months period prevalence of low backache was 67.28%(n=255) while 07 days prevalence was 31.95% (n=124). The prevalence of low back pain was lowest in first year students (7.12%,n=27) and highest in the final year students(33.77%,n=128). Conclusion: High prevalence of low back pain was reported among medical students of United Medical and Dental College Karachi. The prevalence of low back pain was higher among fifth year students, students carrying regular bag packs, those sleeping on soft mattress and in lateral position, those not using backcare cushions and those not doing regular exercise.